Landscape vulnerability to wildfires at the forest-agriculture interface: half-century patterns in Spain assessed through the SISPARES monitoring framework - Ortega, M.; Saura, S.; González-Avila, S.; Gómez-Sanz, V.; Elena-Rosselló, R. (Agroforestry Systems, 2011)
Large-scale socioeconomic changes in recent decades have driven shifts in the structure of Spanish rural landscapes, particularly in those located at the forest-agriculture interface (FAI), as well as in their wildﬁre regime. Using data from more than 200 16 km 2 landscape plots in Spain surveyed between 1956 and 2008 through the SISPARES monitoring framework, we assessed the FAI vulnerability to wildﬁres and identiﬁed the main landscape structural factors related to an increased number of wildﬁre events. We found that the most vulnerable landscapes were those with high road density, high diversity of land uses and, most importantly, with ﬁne-grained forest-agriculture mixtures. Ignition frequency was lower in those landscapes where crops and woodlands coexisted but distributed in large and well-separated patches, and much lower where both land uses were combined within an integrated production and management system (‘‘dehesas’’). We discuss the geographical distribution patterns and temporal trends of the different FAI types during recent decades. We conclude that such approach is useful to forecast the mutual interactions between land use pattern changes and wildﬁre regime in the Mediterranean agroforestry mosaics. This would also provide an ecological base for developing a complementary, cost-effective and durable passive strategy of wildﬁre management targeted to modify the inherent FAI susceptibility to ignition events.
Keywords: agroforestry mosaics; landscape dynamics; spatial pattern vulnerability; structural fire risk; wildfire occurrence